PERBANDINGAN REALISASI NILAI EKSPOR PROVINSI ACEH BERDASARKAN PENGELOMPOKKAN NEGARA TUJUAN SEBELUM DAN MASA PANDEMI COVID-19 - Ulya, Ina Yatul; Anwar, Samsul; Zakia, Ulva (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.11.TAHUN.2022DO - 10.24843/EEB.2022.v11.i11.p07, 2022)
This study aims to group the export destination countries of Aceh Province into 3 categories, namely low, medium and high using the Kmeans clustering method to compare the realization of export values before and during the COVID-19 pandemic. The data employed were secondary data on the export value of Aceh Province to 38 destination countries in 2019 and 2020 which is sourced from the Foreign Trade Statistics of Aceh Province. The results showed a decrease in the average realized export value of Aceh Province during the COVID-19 pandemic. The export value from Aceh Province decreased in 22 countries (57.9%) during the pandemic. The K-means clustering analysis shows that most export destination countries for the Province of Aceh in 2019 and 2020 have low export value realizations. When compared to 2019, the only country that experienced a change in the export value category was Thailand, namely from the low category (cluster 3) to the medium category (cluster 2) during the pandemic. The Aceh government needs to make proactive efforts to increase the realization of export value, for example through adding variety to export commodities, providing subsidies and awards to local exporters and increasing the promotion of the potential of Aceh's resources to the international community.